2D resistivity imaging to determine the distribution of a clay layer and its thickness - M., Reem H.; H., Al-Menshed, F. (Iraqi Journal of Science, 2025)
The aim of the current study is the stratigraphic detection of clay thickness in the Hasciba Al-Sharqi region, western Iraq, which is suitable for making bricks, according to the recommendation of a previous study of the same area. Three resistivity sequences were created with an interelectrode spacing of 5 m, an n factor of 6a (where the initial spacing a is 5 m), and 120 electrodes of the Wenner-Schlumberger array were used. The quality of the 2D data is excellent as shown by the likeness between the pseudosection of the measured and calculated apparent resistivity. As for the quantitative interpretation, it is an inverse model that shows the thickness of the upper part of the Injana Formation (clay layer), ranging from 8 to 17 m. The isopach map shows thickness increases in the eastern part of the study area, with a slight increase in the northwestern side. It increases in the northeastern side, and the reason for this is its proximity to the exposed area north of the study area, as the area is considered a dumping ground for erosion materials. There is also an increase in the thickness value in the center of the study area.  The large amounts of sediment were being swept away to fill burying depressions or levelling the land for construction.